Combining Plato and Jung’s Ideas to Help Youth Overcome Maladaptive Responses and Manage Stress - Janice, Tiffany; Ni Luh Sekar Astuti (Pusat Riset dan Inovasi Nasional, 2026)
Young people often respond to stress through maladaptive patterns such as self-blame, avoidance, emotional withdrawal, and catastrophic thinking. These responses may provide temporary psychological protection, but they can also weaken emotional regulation, resilience, and interpersonal functioning over time. This study examines how Plato’s concept of eudaimonia and Jung’s analytical psychology can be integrated to interpret and address maladaptive responses in youth. Using a qualitative conceptual design supported by exploratory survey data, the study develops an interpretive framework that connects Jungian self-awareness with Platonic virtue-based self-regulation. The survey findings indicate that self-critical and avoidant tendencies were common among respondents, suggesting that many participants struggled to manage stress in reflective and constructive ways. In response, the article argues that Jung’s emphasis on recognizing hidden emotions and inner conflict can deepen psychological insight, while Plato’s emphasis on reason, virtue, and moral formation can guide individuals toward more balanced coping. The study contributes a humanistic framework for youth stress management that links emotional awareness, ethical self-governance, and personal flourishing. It also offers practical implications for educators, counselors, and families seeking more integrative approaches to youth well-being.